Bioactive glasses in restorative dentistry - María Inés Garchitorena (Universidad de la República, 2019)
Bioactive glasses (bg) are ceramic materials whose chemical composition allows them to induce and conduct tissue mineralization. As these glasses can be obtained with the sol-gel method and in nanometric particle sizes, their indication has been extended and enhanced. The antibacterial properties of bg are outstanding: they are possible given the release of ions, which alkalinizes the medium, acting on the bacterial colonies. The medical and dental applications of these materials are wide, with an emphasis on bone regeneration, remineralization of hard dental tissues and treatment of hypersensitivity. However, as they are materials with an amorphous chemical structure, their mechanical properties are not good, this being their main limitation for clinical application in restorative dentistry. In this sense, scientific research has focused on determining the possibility of including bg in various dental materials as a way to combine bioactivity with appropriate mechanical properties. So far, it has not been possible to determine the proportion and methodology necessary to include bg in dental materials without altering their clinical behavior, which is why further research is necessary.